Evolução de um perfil laterítico derivado de BIF em Carajás - SILVA, Aline Cristina Sousa da (2019)
The Carajás Mineral Province (PA) stands out for its richness in iron ore of high grade, the origen of which still raises broad discussion. In this sense, this work uses the changing profile of weathering FN8-0021 borehole in the mine N8 to demonstrate the strong contribution of lateritization in the formation of iron ore...